An air thermostatic system with a thermoelectric cooling within a temperature range from −10 to +90°C for NMR spectrometer probes. Issue 2 (11th September 2017) - Anisimov, Alexander; Dautova, Nailya; Suslov, Maksim
Abstract: In this study, a simple air thermostatic system for a temperature range from ‐10 to +90?C combined with a NMR probe, which can be easily fabricated in a laboratory is proposed. The thermostatic system is suitable for NMR spectrometers for relaxation and diffusion measurement using portable Halbach magnets.